Assessing cellular and genomic damage from environmental nickel using a GFP containing strain of Caenorhabditis elegans - Huffnagle, Ian M. (East Carolina University, 2013)
Nickel is a naturally found mineral that has become widely used for many electronic devices. As use and subsequent discarding of nickel containing products continues exposure to nickel increases. Nickel can cause external superficial symptoms but if it enters the body the potential exists for genomic damage to occur which could lead to mutation and cancer. Nickel can act by generation of reactive oxygen species, interacting with DNA and altering chromatin wrapping. By utilizing a strain of C. elegans with a ced-1::gfp fusion protein, that detects apoptotic cells in the germ line, the deleterious effects of nickel can be analyzed. Analyses of varying concentrations of a water-soluble and an insoluble form of nickel have been done. Insoluble nickel is held to be more hazardous because while soluble easily enters and exits the cell insoluble nickel can remain in the cell for extended periods allowing for much greater damage. The results of this study were inconclusive about the effects of soluble versus insoluble nickel. Previous testing using the C. elegans germline to assess the effects of nickel have used 12 hour exposures (Kezhou et al. 2010). Tests completed in this study exposed animals to lower concentrations of nickel for their full development. A rise in cell deaths is seen as nickel concentration increases which was quantified with ced-1::gfp and Syto12. Analysis using a strain with resistance to heavy metals had no significant increase in engulfments when exposed to nickel, which shows nickel exposure to have been the cause of increased engulfments seen in the wild-type. A lack of increased engulfments in a strain with a mutation to cep-1, the C. elegans homolog of p53, indicated damage from nickel is recognized by the p53 damage pathway.
Keywords: Toxicology; Apoptosis; Ced-1::gfp; Nickel; p53; Toxicity; C. elegans; Nickel--Toxicity testing; Toxicity testing--In vivo; Caenorhabditis elegans